WELCOME TO ARABIC with SESAME STREET - Press, J. P., 1993- (Minneapolis : Lerner Publications, 2020)
Beloved Sesame Street characters show readers basic words and phrases in Arabic so they can connect with new friends who speak the language.
Text in English and Arabic.
Keywords: Arabic language -- Conversation and phrase books -- English -- Juvenile literature